AUTOMATIC TEMPERATURE CONTROL SYSTEM (FULafia Journal of Science and Technology, 2018)
The main thrust of this research is the development of an automatic temperature control system. Temperature is a measure of degree of hotness or coldness of a body or an environment. There are many activities of man where regulation of temperature is not only required but necessary. Typical example of such is the operation of egg incubation unit which requires among others a steady operational temperature. In the present research design, the device operates in such a way that when the temperature is higher than 29°C, a fan is switched on to cool down the environment while at a temperature less than 25°C, a means of raising the temperature istriggered on. In the design, LM35 is employed as temperature sensor and LCD is used to display the ambient temperature while the device has at its heart a PIC18F4550 microcontroller. The developed device can be deployed in the bird’s egg incubation unit for enhanced productivity
Keywords: temperature control; sensor; microcontroller